Wordwall-Assisted Think-Pair-Share for Improving Students’ Mathematics Outcomes - Sondang Noverica (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Mathematics learning requires instructional models that support conceptual understanding, active participation, peer discussion, and repeated practice. However, classroom mathematics instruction often remains dominated by teacher explanation and individual exercises, which may limit students’ engagement and reduce opportunities for collaborative reasoning. This study investigated the effect of Wordwall-Assisted Think-Pair-Share on junior high school students’ mathematics learning outcomes at SMP Katolik Santo Ignatius. The study employed a quasi-experimental pretest-posttest control group design. The sample consisted of 60 students divided into an experimental group and a control group, with 30 students in each group. The experimental group was taught through Think-Pair-Share assisted by Wordwall, while the control group was taught through conventional mathematics instruction. Data were collected using a mathematics learning outcomes test administered before and after the instructional treatment. The data were analyzed using descriptive statistics, N-Gain analysis, paired-sample t-test, and independent-sample t-test. The findings showed that both groups improved after instruction, but the experimental group achieved a substantially higher improvement. The experimental group increased from a pretest mean of 53.47 to a posttest mean of 81.90, with a mean gain of 28.43 and a mean N-Gain of 0.62. The control group increased from a pretest mean of 53.00 to a posttest mean of 68.33, with a mean gain of 15.33 and a mean N-Gain of 0.33. The independent-sample t-test showed a significant posttest difference in favor of the experimental group, p < .001. The study concludes that Wordwall-Assisted Think-Pair-Share is more effective than conventional instruction in improving students’ mathematics learning outcomes. The integration of cooperative discussion and digital practice creates a more interactive, engaging, and conceptually supportive learning environment.